German vision of Russia’s position in the multipolar world (Economic and Political Thought, 2017)
There is a common belief that German society and elites’ attitude to Russiadiffers from the Polish one. It is not the full truth because, as a result ofRussia’s policy, the attitude towards Russia has become much more critical inGermany of the 21st century than it was before. However, Germany carriesout a more global policy than Poland, thus, because of the importance of Germanyand Russia in Poland’s policy, there is an important question what theGerman vision of Russia’s position in the just developing multipolar worldis. The question is even more important as Germany, the strongest state inEurope, stabilising the euro zone, has evident problems with defining itsown role on the international arena and overcoming a one-sided geopoliticalperception of the world.